Use of different carbon sources by strains of Gluconacetobacter diazotrophicus isolated from sugarcane - Barbosa, Edilene Alves; Perin, Liamara; Reis, Veronica Massena (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to quantify the population of Gluconacetobacter diazotrophicus present in plantlets of 34 sugarcane varieties and to characterize the isolates according to their capacity to use carbon sources and produce pink pigments under light. G. diazotrophicus population was estimated using the most probable number technique, and then, isolated in semi-selective culture media. The highest population number of G. diazotrophicus was found in the roots; Brazilian varieties presented the highest population. The isolates used little carbon sources, and those strains obtained from the root used the highest number of carbon sources. Only the strain Ppe-4 and four other ones produce pink pigments under light. The low variation observed may be related to the habitat or to the adaptation of this population to specific internal plant conditions, and for this reason, the genetic structure of these bacteria is limited and preserved.
Keywords: diversity; diazotrophic bacteria; endophytes